Certain Issues Related to the Corpus Delicti of Issuing a Manifestly Unjust Judgment, Verdict, or other Judicial Act - Hovhannisyan, Arman (Bulletin of Yerevan University C: Jurisprudence, 2023)
In the scopes of the present article, certain issues related to the offense of issuing a manifestly unjust verdict, judgment, or other judicial act have been discussed. Analyzing the crime of issuing a manifestly unjust verdict, judgment, or other judicial act, it has been noted that in many countries there is no such crime in the section of crimes against the interests of justice. In the countries that have it, the formulation of the crime is diverse. Though some authors think that the judicial acts mentioned in the Article 482 of the Criminal Code have to resolve the case on the merits, in our opinion, certain other acts like the decision to choose a preventive measure should also be included in the scope of acts. The requirement of having the judicial act reviewed and annulled by higher instances is not mandatory in RA, however, the analysis of the article in detail makes this requirement necessary to prevent abuses. Though certain countries do not require motives as a mandatory element of this crime, we think that motives should be required for the proper qualification of the crimes.